Beyond instructed L2 grammar acquisition: Theoretical insights and pedagogical considerations about the role of prior language knowledge - Angelovska, Tanja (Studies in Second Language Learning and Teaching, 2017)
The prior language knowledge of learners for whom the target language is not the first foreign language poses a different starting learning situation that should merit pedagogical attention. The present paper seeks to contribute to the question of which pedagogical considerations can be made in regard to the role of prior language knowledge beyond instructed L2 grammar acquisition. Moreover, it fills a significant gap expanding the limited existing pedagogical options that instructors have at their disposal when it comes to teaching in classrooms where one foreign language is simultaneously chronologically first to some and second to others. Starting with (combinations of) existing theoretical accounts and associated pedagogical aspects (such as explicit information, negative evidence, metalinguistic explanations, grammar consciousness raising, and input enhancement), a recently developed method (Hahn & Angelovska, 2017) is discussed. The method acknowledges equally the three phases of input, practice and output and is applicable in instructed L2 grammar acquisition and beyond.